Lithium‐Metal Anodes: Incorporating Ionic Paths into 3D Conducting Scaffolds for High Volumetric and Areal Capacity, High Rate Lithium‐Metal Anodes (Adv. Mater. 33/2018). Issue 33 (13th August 2018) - Zhang, Chanyuan; Liu, Shan; Li, Guojie; Zhang, Cuijuan; Liu, Xingjiang; Luo, Jiayan
Abstract : In article number1801328, Jiayan Luo and co‐workers fabricate a mixed ion and electron conducting scaffold for high volumetric and areal capacity, high‐rate lithium‐metal anodes. The well‐dispersed LLZO nanoparticles in the carbon‐nanofiber skeleton improve the electrolyte wettability, homogenize the Li + flux, compensate Li + depletion during plating, and provide excess charge carriers during stripping.